2016
DOI: 10.1088/1742-6596/694/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Determination of small field output factors in 6 and 10 MV flattening filter free photon beams using various detectors

Abstract: Abstract. The study aimed to determine appropriate detectors for output factor measurement of small fields in 6 and 10 MV flattening filter free photon beams using five different detectors. Field sizes were varied between 0.6 × 0.6 and 4.0 × 4.0 cm 2 . An indirect method (daisy-chaining) was applied to normalize the output factors. For the smallest field size, the variations of output factors compared among the detectors were 13%. Exradin A16 had the lowest output factor and increasing in sequence with CC01, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…The OF differences between their study and our study are within ±0.53%. Masanga et al reported OFs for field sizes from 0.6 × 0.6 cm 2 to 4 × 4 cm 2 measured using the Edge detector [20]. The OF differences from our study are within ±0.55% except for a field size of 1 × 1 cm 2 (−1.22% difference).…”
Section: Measurementssupporting
confidence: 54%
“…The OF differences between their study and our study are within ±0.53%. Masanga et al reported OFs for field sizes from 0.6 × 0.6 cm 2 to 4 × 4 cm 2 measured using the Edge detector [20]. The OF differences from our study are within ±0.55% except for a field size of 1 × 1 cm 2 (−1.22% difference).…”
Section: Measurementssupporting
confidence: 54%
“…PDDs were acquired using a PTW (Freiburg, Germany) Semiflex 3D ionization chamber for fields ≥ 4 cm 2 and a PTW microdiamond 19 in the edge-on orientation 20 and a microdiamond in the edge-on orientation for fields < 4 cm 2 , with the detector sitting at 10 cm depth and 90 cm SSD in a water tank. Readings were referenced back to that of 10 × 10 cm 2 through daisy-chaining 21 to calculate output factors.…”
Section: A1 | Pdds and Profiles Of Standard Square Fieldsmentioning
confidence: 99%
“…The increasing output as a function of field size increment is ascribed to back scattered radiation and collimator scatters, which added to primary beam [11]. Such exponential trend of output versus field size has been obtained by Masanga [12]. While the correlation between the output in Gy/Mu versus SSD s at field size of 10×10 cm revealed that: the system output in Gy/Mu has been decreases in logarithmic equation form that could be fitted to = -1.91×ln ( ) + 9.846, where ' ' refers to SSD in cm and ' ' refers to output in Gy/Mu which is due to decreased radiation intensity as shown in Figure (11).…”
Section: Resultsmentioning
confidence: 86%